Evaluation of AES Cryptographic Algorithm on a General-Purpose Map-Scan Accelerator - Pietricica, Andreea-Catalina; Antonescu, Mihai; Popescu, George-Vladut (CAS proceedings, 2023)
As one of the most widely used encryption standards, AES must be implemented taking encryption speed into consideration. This paper presents the evaluation of the AES algorithm on a general-purpose Map-Scan Accelerator. AES proves well suited to a Map style of parallelism, with each computational cell processing one block of data. ECB and CTR modes are implemented and evaluated for key sizes of 128, 192, and 256.